The highest of hopes [large type] - Mason, Susan Anne (Mason, Susan Anne. Canadian crossings, 2019)
After her beloved grandfather's death, Emmaline Moore is shocked to discover that her "deceased" father is actually living in Canada. Having no other family, Emma decides she must find him, and so embarks on a journey across the ocean, accompanied by her best friend, Jonathan. Unfortunately, Randall Moore and his well-to-do family aren't thrilled by her arrival, fearing her sudden appearance will hinder his chance at becoming mayor of Toronto in 1919. Despite everything, Emma remains determined to earn their affection. Jonathan Rowe has secretly loved Emma for years and hopes that during their trip he can win her heart. Concerned that Randall might reject her, Jonathan is ready to console Emma and bring her home. When she informs him that she has no intention of returning to England, Jonathan begins to despair. Can he convince Emma to find value within herself rather than seeking it from a virtual stranger? And will she ever come to see that Jonathan is her true home?